The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages GOOD HOUSEKEEPING. Then there is the matter of "housekeeping" in factories, that is, keeping a factory healthy in the same way as you keep your home healthy. See that it is property ventilated, property cleaned ; that the lavatories work ; that soap and towels are there to wash with and hot and cold water. In the home you would see that these things were properly spaced and that filth and dust were not allowed to accumulate. It is just as important and even more important in factories where so many more people are concerned. Dirt really does mean disease. It is not just a slogan of the Public Health Department. On dirt particles travel the microbes that spread your colds and carry infections from one person to another. T.B. can spread in this way. Dirt is also demoralising. Working in a dirty, filthy place lowers morale. It is very important to maintain health and welfare conditions of the factory at a high level. Recently in the Soviet War News I saw quoted from Pravda an article in which was stressed the fact that everyone was sick and tired of the factory manager who kept his factory in a dirty condition and excused himself by saying "there is a war on." We should pay attention to the manner in which these managers were dealt with in the Soviet Union ; some were heavily punished and a number of them even with loss of citizenship. Now what do we find in our own Chief Inspector's report? He talks about the shortage of labour for this work of factory maintenance and says that tidiness and good "housekeeping" are down to a minimum. This is absolutely wrong. It should not be down to a minimum. Take this example which is an interesting one as well as being instructive. You know that with bad lighting in a factory morale goes down. But other things happen too. Accidents go up and there are more "rejects." There has been some useful work done by the Industrial Health Research Board on efficiency in relation to lighting. If you want to bring up to the level of good workers, those not quite so good, probably the most important thing to give them is a really good light. It is quite surprising, the effect of light on efficiency. There is an interesting reference to a shell factory lighting. — when the intensity of light fell from 14 foot candles to 10.5 in 30 days, solely from the accumulation of dust on the lights and reflectors. The point about this "housekeeping" side of factory health is that it is such a simple thing to deal with. You will add enormously to the health of factories by paying attention to the "housekeeping" side. You do not need 4 years of training as a medical man to do it. Practically any of the women, such excellent housekeepers in their own homes and now working in factories, could do it. There are very few good housekeeping women now working in factories who could not do a good job to clear up factories throughout the country. The Ministry of Health had a drive for cleaning up cow sheds. There was on incentive, because if cow sheds were cleaned up and other standards of cleanliness observed the cowmen got more milk. Many of them said it was impossible to clean up their cow sheds. But, they set 7 15X/2/103/295